2015
DOI: 10.1310/hpj5004-279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drug Shortages on Health System Pharmacies in the Southeastern United States

Abstract: Background:Drug shortages have become all too common and affect all aspects of the health care delivery system. The increased number of drug shortages has had a negative impact on patient care as well as costly financial implications. Objectives: This article identifies the current problems and negative outcomes drug shortages have caused and provides a framework for how to best prepare for and combat future shortages. It highlights specific problems faced by health care system pharmacies in the Southeastern U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 22 publications
2
46
1
1
Order By: Relevance
“…We believe this is the first comprehensive study among public sector hospitals in South Africa to review the current situation regarding therapeutic interchange policies following NDoH guidance [25]. The response rate of 33.5%, despite sending up to 12 reminders, which was similar to one study conducted in the US (40%) [31]; however, it was higher than studies in Europe and another study in the US with response rates of 22% and 13%, respectively [29,32]. Pharmacy managers provided the highest number of responses (Table 2), similar to a study conducted in the US [33].…”
Section: Discussionsupporting
confidence: 58%
“…We believe this is the first comprehensive study among public sector hospitals in South Africa to review the current situation regarding therapeutic interchange policies following NDoH guidance [25]. The response rate of 33.5%, despite sending up to 12 reminders, which was similar to one study conducted in the US (40%) [31]; however, it was higher than studies in Europe and another study in the US with response rates of 22% and 13%, respectively [29,32]. Pharmacy managers provided the highest number of responses (Table 2), similar to a study conducted in the US [33].…”
Section: Discussionsupporting
confidence: 58%
“…The median time spent observed per hospital in this study (± two hours a week) is much lower than the previously reported time spent of hospital pharmacies on supply problems [4, 5, 15, 25, 26]. According to the European association of hospital pharmacists (EAHP), the time spent was measured through a survey and ranges between one hour a week and 15 hours a week [4].…”
Section: Discussionmentioning
confidence: 70%
“…As discussed above, a higher stock at hospital pharmacies can help to overcome short-term supply disruptions. Keeping a buffer and a well-managed stock is also important to avoid managed inventory shortages [26]. This was confirmed by hospital pharmacists in the validation session.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Exploring the problems and the negative outcomes of DSs, Clauder et al have conducted a survey among pharmacy directors in North Carolina, South Carolina, Georgia, and Florida [11]. Responders reported that DSs cause 1 to 5% error rates in hospitals, and 60% of the time DSs create unsafe conditions for patients and staff.…”
Section: Introductionmentioning
confidence: 99%